Hoof beats could mean zebras: A rare late metastasis of breast carcinoma in the rectum - Mishra, Rupa; Joshi, Sneha; Thakkar, Deepti; Nare, Smeeta; Koppiker, CB (Indian Journal of Case Reports, 2024)
Breast cancer metastasis is most commonly observed in bone, lung, liver, and brain and is rarely observed in the gastrointestinal tract (GI). In rarer cases, GI metastasis reaches the rectum and generally presents as late metastasis. The type of breast cancer usually associated with GI metastasis is invasive lobular carcinoma; however, few case reports also show their association with invasive ductal carcinoma (IDC). Here, we report a case that unfortunately is a coalescence of all these atypical events, with metastatic rectal linitis plastica (RLP) of the breast, 15 years after the treatment of the primary tumor, originating from IDC. This is the first case report from India, reporting the late metastatic presentation of breast cancer as RLP. The report emphasizes the need to correlate persistent GI symptoms to breast cancer history; however, late the presentation may be.